Environmental correlates of adolescent active travel to school in Asia: An ecological study. (May 2023) - Maulida, Rizka; Goel, Rahul; Labib, S.M.; Oni, Tolu; van Sluijs, Esther MF.
Abstract: Objectives: This study aimed to examine the association between country-level environmental correlates and the prevalence of active school travel (AST) in Asia and country-level differences in AST by age and sex. Methods: This ecological study involved 31 Asian countries. Dependent variables were AST prevalence, AST prevalence difference by age, and by sex. Independent variables were country-level environmental correlates extracted using publicly available datasets, classified into physical and social environments. Association estimates of each dependent variable and each of the independent variables were calculated using univariate linear regression. All variables were standardized to have a mean of 0 and a standard deviation of 1. Results: Results showed that 1 standard deviation (SD) difference in urban population percentage, night-time light, secondary-school enrolment, and prevalence of adult insufficient physical activity were negatively associated with AST prevalence (SD difference: −0.44 (−0.78 to −0.09), −0.40 (−0.76 to −0.04), −0.39 (−0.74 to −0.04), and −0.40 (−0.76 to −0.03), respectively). A 1 SD difference in car per people was associated with a −0.46 (−0.84 to −0.09) difference of AST prevalence by age. A 1 SD difference in PM2.5 concentration and of prevalence of adult insufficient physical activity were associated with a difference of 0.38 (0.01–0.74) and 0.42 (0.03–0.80) difference of AST prevalence by sex. Conclusions: This study shows that Asian countries with a greater number of people living in urban areas, lower levels of overall adult physical activity and higher levels of night-time light have a lower prevalence of adolescent AST. Country-level physical and social environmental correlates explained some of the regional variance in AST. Future policy actions and interventions for the region need to be contextually sensitive to the environmental correlates that vary between countries. Highlights: Country-level factors explain some of regional variance in active travel to school. Lower prevalence of AST in countries with greater population living in urban areas. Lower prevalence of AST in countries less supportive of general physical activity. Future policy actions and interventions need to be contextually sensitive.